PENERAPAN FUNGSI-FUNGSI MANAJEMEN DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM - Firdaus Jeka; Samsu; Tuti Indriyani; Asrulla (LPPM Universitas Cipta Mandiri, 2024)
This paper discusses in depth about the functions of management, namely planning, organizing, actuating, and controlling abbreviated as POAC. The method used is literature study and document analysis to obtain theories or writings related to it. The result of this paper is that Management is both a science and an art, meaning that management in its implementation must always consider the appropriate situation and conditions with the specified goals. Therefore, management has various functions that must be understood in a complete and comprehensive manner. Based on the management process as stated by the experts, the management experts of the present era abstract it into 4 processes, namely planning, organizing, actuating, controlling (POAC). The planning function begins with the mechanism of determining the direction and goals to be achieved. The implementation function is carried out by dividing tasks, responsibilities, connecting and unifying tasks and functions within the organization or institution. The supervision function is carried out by controlling the quantity and quality of work results through measurement and assessment systems.